Regioselectivie Synthesis of New Spiro-Oxindolopyrrolidines via a Three-Component Asymmetric 1,3-Dipolar Cycloaddition Reaction of Azomethine Ylides aAnd Chiral Menthyl Cinnamate - M. J. Taghizadeh; F. Salahi; M. Hamzelooian; K. Jadidi (Journal of Sciences, Islamic Republic of Iran)
An efficient, one-pot, four-component procedure for the synthesis of a small library of new chiral spiro- oxindolopyrrolidines with high regio-, diastereo- (>99:1 dr), and enantioselectivity (up to 80% ee) is described. In this process, the regio- and stereochemical 1,3-dipolar cycloaddition of azomethine ylides, which were generated insitu by the reaction of isatin derivatives and sarcosin,with optically active chiral menthyl cinnamate studied on the basis of the assignment of the absolute configuration of the cycloadducts, and on theoretical calculations. In comparison with active cinnamoyl oxazolidinone, when the reactions were performed with active chiral menthyl cinnamate as dipolarophile, a remarkable unexpected inversion in the regioselectively was observed. The regioselectivity of the reactions was investigated using global and local reactivity indices at the B3LYP/6-311G(d,p) level of theory. The effects of the electronic and steric factors on the regioselectivity of the reactions were discussed. The electronic structures of critical points were studied by the natural bond orbital (NBO) method.